The Princess in Black and the science fair scare - Hale, Shannon; Hale, Dean, 1972-; Pham, LeUyen (Somerville, Massachusetts : Candlewick Press, 2018)
Princess Magnolia is excited. Excited and nervous. She's going to the Interkingdom Science Fair today to present her poster about seeds and plants, and when she arrives, she sees that her friends are there too! Princess Honeysuckle made a mole habitat, Princess Sneezewort has built a blanket fort, and Tommy Wigtower has a talking volcano that's saying 'EAAAAT!' Wait, what? A surprise goo monster makes this a job for the Princess in Black, and the Princess in Blankets is on the scene to lend a hand. But will two masked heroes be enough to save the science fair?
Kirkus Review, August 2018
3.0.
K-3.
500L
L
Keywords: Superheroes -- Juvenile fiction; Science fairs -- Juvenile fiction; Princesses -- Juvenile fiction; Friendship -- Juvenile fiction; Superheroes -- Fiction; Science fairs -- Fiction; Princesses -- Fiction; Friendship -- Fiction; Fantasy fiction